Learning about COVID-19: a qualitative interview study of Australians' use of information sources - Deborah Lupton; Sophie Lewis (BMC, 2021)
Abstract Background A multitude of information sources are available to publics when novel infectious diseases first emerge. In this paper, we adopt a qualitative approach to investigate how Australians learnt about the novel coronavirus and COVID-19 and what sources of information they had found most useful and valuable during the early months of the pandemic. Methods In-depth semi-structured telephone interviews were conducted with a diverse group of 40 Australian adults in mid-2020 about their experiences of the COVID-19 crisis. Participants were recruited through Facebook advertising. Detailed case studies were created for each participant, providing the basis of a thematic analysis which focused on the participants' responses to the questions about COVID-19-related information sources. Results Diverse sources of COVID-19-related information, including traditional media, online media and in-person interactions, were actively accessed, appraised and engaged with by participants. There was a high level of interest in COVID-19 information as people grappled with uncertainty, anxiety and feeling overwhelmed. Certain key events or experiences made people become aware that the outbreak was threatening Australia and potentially themselves. Most people demonstrated keen awareness that misinformation was rife in news outlets and social media sites and that they were taking steps to determine the accuracy of information. High trust was placed in health experts, scientists and government sources to provide reliable information. Also important to participants were informal discussions with friends and family members who were experts or working in relevant fields, as well as engaging in-person in interactions and hearing from friends and family who lived overseas about what COVID-19 conditions were like there. Conclusion A constantly changing news environment raises challenges for effective communication of risk and containment advice. People can become confused, distressed and overwhelmed by the plethora of information sources and fast-changing news environment. On the other hand, seeking out information can provide reassurance and comfort in response to anxiety and uncertainty. Clarity and consistency in risk messaging is important, as is responding quickly to changes in information and misinformation. Further research should seek to identify any changes in use of and trust in information sources as time goes by.